(untitled) (Journal of the College of Languages (JCL), 2025)
In his masterpiece ’The Prophet’, Kahlil Gibran presents his unwavering faith and passionate belief in the healing power of universal love that brings humans to sublime ideas and elevates their souls and behavior. The current study aims to find out the stylistic devices utilized to represent the concept of love based on the hypothesis that Gibran tends to use certain stylistic effects to convey his meaning. The study adopts Leech and Short’s (2007) framework of stylistic analysis to analyze the lexical items and figures of speech in selected extracts from the book. The findings reveal that Gibran prefers concrete nouns, dynamic verbs, and physical adjectives over abstract nouns, stative verbs, and psychological adjectives to show his energetic and realistic perspective on love. Finally, for figures of speech, Gibran mostly depends on personification referring to love as a person capable of doing actions (beckons to you, gathers you, etc.) besides simile and metaphor.